COVID-19 Transmission Within a Family Cluster in Yancheng, China - Zhang, Hongming; Chen, Runzhe; Chen, Jibei; Chen, Baoan (Frontiers in Medicine, 2020)
We report the clinical features of novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in a family setting of 13 people with person-to-person transmission in Yancheng, Jiangsu Province, China.